Effects of organic fertilizer incorporation practices on crops yield, soil quality, and soil fauna feeding activity in the wheat-maize rotation system - Zhou, Zhongkai; Zhang, Siyu; Jiang, Na; Xiu, Weiming; Zhao, Jianning; Yang, Dianlin (Frontiers in Environmental Science, 2022)
The decline in soil quality is becoming a significant process of soil degradation. Optimizing organic fertilizer incorporation practices in cropland is essential to enhancing crop productivity and soil health. However, that requires a comprehensive understanding of crop yield and soil quality reaction across an application gradient of organic fertilizer. We investigated the effect of organic fertilizer incorporation practices on crop yield, soil quality, and fauna feeding activity from fluvo-aquic soils on wheat (Triticum aestivum)-maize (Zea mays) rotation field. The six treatments included were unfertilized N control (UC), traditional chemical fertilizer application (TF, 600 N kg·ha-1·year-1), and recommended chemical fertilization (RF, 400 N kg·ha-1·year-1) with no organic fertilizer application rate, low-level 15.0 (RFLO), medium-level 30.0 (RFMO), and high-level 45.0 t·ha-1·year-1 (RFHO) application, respectively. The research findings show that the yield with organic fertilizer incorporation treatments increased 26.4%-44.6% for wheat and 12.5%-40.8% for maize compared to RF plots. The long-term organic fertilizer incorporation rate increased organic carbon from 54.7% to 110.6% versus UC plots and 27.9% to 74.0% versus chemical fertilizer (TF and RF) treatments, and the total nitrogen content of soil increased from 41.8% to 59.2%, and 24.6% to 39.2%. The long-term inorganic fertilizer combined with organic fertilizer incorporation practices significantly enhanced soil sucrose (30.1%-51.9%), urease (28.4%-38.3%), and β-1,4-glucosidase (34.6%-122.4%) activity. Still, nitrite reductase, polyphenol oxidase, and catalase significantly lower 27.3%-49.9%, 8.5%-26.3% and 23.3%-34.3% than single applications of inorganic N fertilizer groups. Meanwhile, the results showed that organic fertilizer incorporation practices improved soil fauna feeding activity by 35.2%-42.5%, and the excessive application of inorganic N fertilizer reduced the activity level of soil fauna.